Biomarker development on alcohol addiction using EEG - Vuong, P.L. (2013)
Alcohol addiction is harmful to society, economy and personal health. Alcohol addiction treatments intend to help addicted individuals reduce and stop compulsive alcohol use. Using biomarker, the clinicians could determine if drugs are having a desirable effect much earlier and given in correct dose for treatment. This paper will provide an up-to-date review of the state of the art in biomarker development for alcohol addiction treatment using electroencephalography (EEG) including EEG methodologies and their applications. Â© Springer-Verlag 2013.